Revisiting Landmark Trials: How DCB Therapy and Plant-Based Diets Transform Chronic Coronary Syndrome Care - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
Landmark trials, from COURAGE to ISCHEMIA, have profoundly influenced clinical guidelines by emphasizing optimal medical therapy (OMT) as the primary management strategy for chronic coronary syndrome (CCS) due to limited incremental benefits demonstrated by invasive percutaneous coronary interventions (PCI) utilizing conventional stents. However, significant advancements in Drug-Coated Balloon (DCB) technology and Plant-Based Diet (PBD) strategies have demonstrated exceptional clinical outcomes, dramatically reshaping the therapeutic landscape. Clinical results, including exceedingly minor procedural complications, low rates of repeat revascularization, minimal restenosis (<2%), complete elimination of stent thrombosis, and markedly reduced bleeding risks associated with abbreviated or eliminated dual antiplatelet therapy (DAPT), are primarily attributed to meticulous lesion preparation protocols and diet-driven systemic improvements. This review comprehensively discusses these novel findings, exploring their implications for updating clinical guidelines. Real-world data from Bethsaida Hospital, chaired by Prof. Dasaad Mulijono, substantiates these outcomes, emphasizing the clinical superiority of integrating advanced DCB therapies and PBD, suggesting the need to revisit foundational conclusions drawn from previous landmark trials.